A Retrospective Study of Cognitive Improvement Following Electroconvulsive Therapy in Schizophrenia Inpatients. Issue 3 (September 2019) - Seow, Lee Seng Esmond; Subramaniam, Mythily; Chan, Yi Wen Christopher; Martin, Donel M.; Abdin, Edimansyah; Chong, Siow Ann; Liu, Jianlin; Peh, Chao Xu; Tor, Phern Chern
Abstract : Objectives: Findings on the cognitive effect of electroconvulsive therapy (ECT) in individuals with schizophrenia have brought mixed results, with few recent studies beginning to report cognitive improvements after treatment. Cognitive change in inpatients with schizophrenia who were referred for an acute course of ECT was examined in the current study. Furthermore, the study aimed to determine the profile of patients who experience cognitive improvement and the potential use of a brief cognitive battery to detect this positive cognitive change, if any. Methods: Montreal Cognitive Assessment (MoCA) was conducted at baseline and posttreatment after 6 sessions of ECT. The Brief ECT Cognitive Screen was also administered to determine its predictive ability on cognitive gain of 2 points or higher in MoCA total scores for the 2 consecutive time points. Results: A total of 81 inpatients were included in the study. Retrospective analysis revealed significant improvements in MoCA total score and domains of visuospatial/executive function and attention. Cognitive improvement was more pronounced among those who had worse pre-MoCA score before ECT. Conclusions: The study provided support to the existing literature where cognitive improvement has been reported among individuals with schizophrenia after ECT. Future studies should consider the use of randomized controlled trials to examine the possible cognitive benefits of ECT. In a setting where there is a high volume of patients receiving ECT, the monitoring of patients' cognitive status through the course of ECT continues to be warranted and the Brief ECT Cognitive Screen may be useful as a quick measure to detect such ECT-related cognitive change. Abstract : Supplemental digital content is available in the text.